APPLICATION OF THE CLOND TECHNOLOGIES IN THE PROCESS OF STUDYING. THE CYCLE OF PROFESSIONALLY ORIENTED HUMANITARIAN, SOCIAL AND ECONOMIC PREPARING THE FUTURE PVIMARY SCHOOL TEACHERS. (Journal of Information Technologies in Education (ITE), 2013)
The article depicts the innovative approaches in preparing the future primary school teachers which aim. Their competence in mastering the sphere of planning the secondary school work. It is realized by means of the cloud cervices. The introduction of the organizer SkyDrive into the studying process of higher education establish ments strengthens students cognitive activity,stimulates their creativity, helps the formation of professional skills and habits as well as their competiveness in general.
Keywords: information technologies; cloud services; Sky Drive; chat-consultation; planning he secondary school work; “Shkoloznavstvo”